(untitled) (International Journal of Nursing Education, 2020)
Background of the Study: The term ‘adverse event’ describes harm to the patient as a result of medical care. Patient safety event reporting systems are ubiquitous in hospitals and are a mainstay of efforts to detect patient safety and quality problems. Incident reporting is frequently used as a general term for all voluntary patient safety event reporting systems which rely on those involved in events to provide detailed information. Aim: To assess the knowledge, attitude and perceived barriers to incident reporting among the staff nurses working in a tertiary care hospital, Ludhiana. Methodology: A descriptive study was conducted in the month of May 2017 in Dayanand Medical College and Hospital, Ludhiana. A total of 60 staff nurses were selected by convenient sampling technique and 4 parts of tools were used for the collection of data. The tools included socio-demographic profile, Questionnaire to assess the knowledge, Likert scale to assess the attitude and a Checklist to assess the perceived barriers. Validity of the research tool was established under the guidance of research supervisor and other experts. Result: Most of the staff nurses working in DMC & H, Ludhiana had average knowledge and positive attitude towards incident reporting and the co-relation of knowledge and attitude came out to be weakly positive. Conclusion: The staff nurses had average knowledge, positive attitude towards the incident reporting. There was weak positive correlation between knowledge and attitude of staff nurses. Fear of legal action, too busy/ lack of time and fear of career/ personal reputation were the common perceived barriers by staff nurses regarding incident reporting.